Highly Crystalline CVD-grown Multilayer MoSe2 Thin Film Transistor for Fast Photodetector - Jung, Chulseung; Kim, Seung Min; Moon, Hyunseong; Han, Gyuchull; Kwon, Junyeon; Hong, Young Ki; Omkaram, Inturu; Yoon, Youngki; Kim, Sunkook; Park, Jozeph (NATURE PUBLISHING GROUP, 2015)
Hexagonal molybdenum diselenide (MoSe2) multilayers were grown by chemical vapor deposition (CVD). A relatively high pressure (>760 Torr) was used during the CVD growth to achieve multilayers by creating multiple nuclei based on the two-dimensional crystal growth model. Our CVD-grown multilayer MoSe2 thin-film transistors (TFTs) show p-type-dominant ambipolar behaviors, which are attributed to the formation of Se vacancies generated at the decomposition temperature (650 degrees C) after the CVD growth for 10 min. Our MoSe2 TFT with a reasonably high field-effect mobility (10 cm(2)/V.s) exhibits a high photoresponsivity (93.7 A/W) and a fast photoresponse time (tau(rise) similar to 0.4 s) under the illumination of light, which demonstrates the practical feasibility of multilayer MoSe2 TFTs for photodetector applications.
Keywords: CHEMICAL-VAPOR-DEPOSITION; LARGE-AREA; LAYER MOSE2; ATOMIC LAYERS; MONOLAYER; PHOTOTRANSISTORS; BANDGAP